Menikahi Wanita Manapun yang Disukai Selain Dari Anak Yatim dalam Surat An-Nisa Ayat 3 Studi Tafsir Ibnu Katsir - Adrianto, Adrianto; Haslinda, Haslinda; Sitorus, Chalid (Institut Darul Quran Payakumbuh, 2025)
Abstract This study aims to describe Increasing marry any woman you like except an orphan on Al-Quran Surat An-Nisa Ayat 3 Studi Tafsir Ibnu Katsir the data collection technique is using library research or library study research with data collection techniques carried out by examining literature, document, and other sources of information related to the Topik of researchers. The result of this study the first, Surat An-Nisa (4:3) which sounds And if you are afraid you won't be able to do it fair towards (the rights of) orphaned women if you marry him), then marry (other) women which one you like: two, three or four. This verse discusses the possibility polygamy in Islam and the requirements that must be met to do so The second, this ayat offering polygamy (marrying more than one wife) as a solution, provided that a person is able to act fair towards all his wives If someone is unable to do so fair then it is advisable to only marry one wife or even just marry a slave The third this ayat o give an overview of law polygamy in Islam that is, it is permitted with the main condition able to apply fair If unable to do so fair then it is advisable to only marry one wife or even a slave